Mary M. Veeneman. Introducing Theological Method: A Survey of Contemporary Theologians and Approaches - Tkachenko, Rostislav (Bogoslovskie razmyšlenija, 2019)
Book review:Introducing Theological Method: A Survey of Contemporary Theologians and Approaches. By Mary M. Veeneman. Grand Rapids, MI: Baker Academic, 2017. vi + 202 pp.; ISBN: 9780801049491 (pbk.); 24.99 USD.